SLC26A3 inhibitor identified in small molecule screen blocks colonic fluid absorption and reduces constipation - Peter M. Haggie; Onur Cil; Sujin Lee; Joseph-Anthony Tan; Amber A. Rivera; Puay-Wah Phuan; Alan S. Verkman (JCI Insight, 2018)
SLC26A3 (downregulated in adenoma; DRA) is a Cl–/anion exchanger expressed in the luminal membrane of intestinal epithelial cells, where it facilitates electroneutral NaCl absorption. SLC26A3 loss of function in humans or mice causes chloride-losing diarrhea. Here, we identified slc26a3 inhibitors in a screen of 50,000 synthetic small molecules done in Fischer rat thyroid (FRT) cells coexpressing slc26a3 and a genetically encoded halide sensor. Structure-activity relationship studies were done on the most potent inhibitor classes identified in the screen: 4,8-dimethylcoumarins and acetamide-thioimidazoles. The dimethylcoumarin DRAinh-A250 fully and reversibly inhibited slc26a3-mediated Cl– exchange with HCO3–, I–, and thiocyanate (SCN–), with an IC50 of 0.2 μM. DRAinh-A250 did not inhibit the homologous anion exchangers slc26a4 (pendrin) or slc26a6 (PAT-1), nor did it alter activity of other related proteins or intestinal ion channels. In mice, intraluminal DRAinh-A250 blocked fluid absorption in closed colonic loops but not in jejunal loops, while the NHE3 (SLC9A3) inhibitor tenapanor blocked absorption only in the jejunum. Oral DRAinh-A250 and tenapanor comparably reduced signs of constipation in loperamide-treated mice, with additive effects found on coadministration. DRAinh-A250 was also effective in loperamide-treated cystic fibrosis mice. These studies support a major role of slc26a3 in colonic fluid absorption and suggest the therapeutic utility of SLC26A3 inhibition in constipation.